Method for extracting pure natural crystalline flake graphite through selective flotation of modified water glass

By using acidified and salted modified water glass for flotation, the problem of waste and inhibition of low-grade natural scale graphite mineral resources in the prior art is solved, efficient recycling and enrichment is achieved, and fixed carbon is significantly improved Content and recovery rate.

CN119425963AActive Publication Date: 2025-02-14KUNMING UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411274774.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-02-14
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover useful minerals in low-grade natural scale graphite ore, resulting in waste of resources. In some cases, the inhibition effect of traditional water glass is not ideal, the cost is high, and the selective inhibition effect has not been significantly improved.

Method used

Acidified modified water glass and salted modified water glass are used to flotation low-grade and high-grade natural scale graphite ore respectively. The modified water glass is modified by ultrasonic treatment, making its molecules smaller and more dispersible, and enhancing graphite Selectivity with impurities.

Benefits of technology

The fixed carbon content and recovery rate of scale graphite are significantly improved, the inhibitory effect on ganglionic minerals is enhanced, and the better enrichment of scale graphite and efficient recovery of resources are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425963A_ABST
    Figure CN119425963A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mineral processing, and particularly relates to a method for extracting pure natural crystalline flake graphite through selective flotation of modified water glass. According to the method, different modified water glass is adopted for different graphite ores for the first time, and the product with high fixed carbon content and high recovery rate is obtained through cooperation of the flotation technology. The method comprises the following steps: crushing and grinding natural crystalline flake graphite ore to set fineness, then mixing with water to prepare ore pulp, adding a pH regulator to regulate the pH of the ore pulp, then adding modified water glass according to a set dosage, then sequentially adding a collecting agent and a foaming agent, and finally carrying out air inflation and foam scraping to obtain flotation concentrate. The process is simple and controllable, the fixed carbon content of the product obtained through roughing can be further improved after fine selection, and industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mineral processing, and in particular relates to a method for selectively flotating and purifying natural flake graphite by modified water glass. Background Art

[0002] As a vital non-metallic strategic resource, graphite has many irreplaceable advantages such as excellent electrical conductivity, thermal conductivity, corrosion resistance and lubricity. In economic development, graphite is widely used in many key industries, from high-tech electronics to traditional industrial fields. It occupies a pivotal position and provides a solid guarantee for promoting sustainable economic development and technological progress.

[0003] Natural graphite ore is mainly divided into flake graphite and microcrystalline graphite. Flake graphite is mainly used in cutting-edge technology raw materials such as battery raw materials and atomic energy. With the continuous development of science and technology, high-grade flake graphite ore is decreasing; at the same time, countries have listed flake graphite ore as a strategic resource to restrict its export, so the development and utilization of low-grade flake graphite ore is particularly important. Low-grade flake graphite stone presents the characteristics of low grade, fine embedded particle size and complex composition. It is difficult to achieve selective inhibition using a single water glass as an adjusting agent, resulting in the inability to effectively recover useful minerals in mineral resources, resulting in a waste of resources. In order to recover the target minerals from the original ore as much as possible and improve the flotation index, it is necessary to use other adjusting agents or modify the water glass. The former not only requires a higher cost, but also has no significant improvement in the selective inhibition effect when processing complex and difficult-to-select ores. The cost of modifying water glass is low, which can greatly enhance its selective inhibition effect. .

[0004] Deng Jie published an article titled "Flotation separation of barite from calcite using acidified water glass as the depressant" in "Colloids and Surfaces A: Physicochemical and Engineering Aspects". In the calcite flotation test, water glass and acidified water glass prepared with sodium silicate and sulfuric acid were used as depressants. Studies have shown that when single water glass is used as a depressant, the separation effect is not ideal. When the same dosage of acidified water glass is used, the recovery rate of barite remains almost unchanged, but the recovery rate of calcite drops below 10%, achieving effective separation of barite and calcite. Yang Yaohui published an article titled "Selective flotation of ilmenite from olivine using the acidified water glass as depressant" in the International Journal of Mineral Processing. Water glass and oxalic acid-acidified water glass were used as depressants to depress olivine and thus float ilmenite. It was found that compared with water glass, acidified water glass not only increased the recovery rate and grade of Ti concentrate by 7.74 percentage points and 3.82 percentage points respectively, but also reduced the consumption of depressants by 2 / 5. Feng Bo published an article titled "The flotation separation of scheelite from calcite using acidified sodium silicate as depressant" in Minerals Engineering. Calcite and scheelite were separated by flotation using water glass and oxalic acid-acidified water glass as depressants. It was found that when using only water glass as a depressant, the recovery rates of scheelite and calcite were both around 80%, and the flotation separation of scheelite and calcite could not be achieved. When using acidified water glass as a depressant, the recovery rate of scheelite remained almost unchanged, but the recovery rate of calcite dropped to less than 20%.

[0005] He Jingfeng published an article titled "Combined inhibitors of Fe 3+ ,Cu 2+ orAl 3+and sodiumsilicate on the flotation offluorite and quartz》 used fluorite and quartz samples to study the flotation offluorite and quartz. 3 + , Cu 2+ and Al 3+ The effect of separately salted water glass on fluorite flotation. The test results show that when Cu-water glass is used as a depressant under the optimal conditions, the recovery rate of fluorite is 83.56%, while the recovery rate of quartz is 6.09%, achieving efficient separation of fluorite and quartz; Wei Zhao published an article titled "Al-Na 2 SiO 3 Mechanism of polymer depressants in flotation separation of scheelite and calcite》Al-water glass prepared with sodium silicate and aluminum sulfate in a mass ratio of 2:1 was used as a depressant, and Pb-BHA complex was used as a collector to separate scheelite from calcite. It was found that when water glass was used alone as a depressant, calcite minerals were enriched to a certain extent. When Al-water glass was used as a depressant, a concentrate with a scheelite recovery rate of 89.8% and a calcite recovery rate of 27% was obtained, achieving a better separation effect.

[0006] It can be seen that in the prior art, acidified modified water glass or salted modified water glass is generally used for flotation of calcite, ilmenite, scheelite, and fluorite. There are few reports on the use of modified water glass for flotation of natural flake graphite. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention attempts for the first time to use different modified water glasses to float natural flake graphite.

[0008] Low-grade natural flake graphite (such as low-grade natural flake graphite ore with a fixed carbon content of less than or equal to 9%) is characterized by being poor, fine and impure. When water glass is used as a single adjusting agent, it is difficult to achieve the purpose of selective inhibition, resulting in the inability to effectively recover useful minerals in mineral resources, causing a waste of resources. Using other adjusting agents requires higher costs, and when processing complex and difficult-to-select ores, the selective inhibition effect is not significantly improved. The present invention provides a method for flotation purification of low-grade natural flake graphite by acidified modified water glass, which aims to enhance the selectivity of graphite and various impurities, can more effectively inhibit gangue minerals, enable better enrichment of flake graphite, and improve its fixed carbon content and recovery rate.

[0009] For natural flake graphite ores with a fixed carbon content of 35% or more, the traditional water glass has an unsatisfactory inhibitory effect in some cases, and the cost of using other inhibitors is high, and when processing complex and difficult-to-select ores, the selective inhibitory effect is not significantly improved. The present invention provides a method for flotation purification of natural flake graphite by salt-modified water glass, which aims to enhance the selectivity of graphite and various impurities, can more effectively inhibit gangue minerals, enable better enrichment of flake graphite, and improve its fixed carbon content and recovery rate.

[0010] The present invention provides a method for selectively flotating and purifying natural flake graphite by modified water glass, comprising the following schemes: Scheme 1

[0011] (1) crushing and grinding a low-grade natural flake graphite ore having a fixed carbon content of 9% or less until the grinding particle size of -200 mesh accounts for more than 90% to obtain flake graphite ore powder;

[0012] (2) transferring the flake graphite ore powder obtained in step (1) to a flotation tank and mixing it with water at a slurry concentration of 10 wt.% to 22 wt.%, stirring to obtain a slurry;

[0013] (3) adding a pH adjuster to the slurry obtained in step (2) to adjust the pH of the slurry to 5 to 8, and stirring to obtain a slurry with adjusted pH;

[0014] (4) Adding acidified modified water glass in an amount of 700-1100 g / t to the slurry after pH adjustment and stirring. The amount here is calculated based on the water glass before modification;

[0015] (5) adding a collector in an amount of 270 to 420 g / t to the slurry containing acidified modified water glass obtained in step (4), and stirring;

[0016] (6) adding a frother in an amount of 200 to 390 g / t to the slurry to which the collector is added obtained in step (5), stirring, turning on the aeration switch, and then performing flotation by scraping, filtering and drying the scraped foam to obtain No. 1 flake graphite concentrate;

[0017] Solution 2

[0018] (A) crushing and grinding natural flake graphite ore having a fixed carbon content of 35% or more until the grinding particle size of -200 mesh accounts for more than 80% to obtain flake graphite ore powder;

[0019] (B) transferring the raw graphite flake powder obtained in step (A) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 20 wt.%, stirring to obtain a pulp;

[0020] (C) adding a pH adjuster to the slurry obtained in step (B) to adjust the pH of the slurry to 9 to 11, and stirring;

[0021] (D) adding 600-900 g / t of salt-modified water glass to the pH-adjusted slurry obtained in step (C), and stirring, wherein the amount is calculated based on the water glass before modification;

[0022] (E) adding a collector in an amount of 360 to 540 g / t to the slurry containing salt-modified water glass obtained in step (D), and stirring;

[0023] (F) adding a frother in an amount of 220-450 g / t to the ore pulp to which the collector is added obtained in step (E), stirring, turning on the aeration switch, and then performing flotation by scraping, filtering and drying the scraped foam to obtain No. 2 flake graphite concentrate.

[0024] Preferably, the present invention provides a method for selectively flotating and purifying natural flake graphite by modified water glass, wherein the first scheme comprises the following steps:

[0025] (1) A low-grade natural flake graphite ore having a fixed carbon content of 9% or less is coarsely crushed by a crusher to 8 to 35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1 to 3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 to 5 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0026] (2) transferring the flake graphite ore obtained in step (1) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 22 wt.%, and stirring for 1 to 3 minutes to obtain a pulp;

[0027] (3) adding a pH adjuster to the slurry obtained in step (2) to adjust the pH of the slurry to 5 to 8, and stirring for 2 to 5 minutes;

[0028] (4) After the acid and water glass are modified, 700-1100 g / t of acidified modified water glass is added to the pH-adjusted slurry and stirred for 2-5 min. The amount here is calculated based on the water glass before modification.

[0029] (5) adding a collector in an amount of 270 to 420 g / t to the slurry to which the acidified modified water glass is added, and stirring for 2 to 5 minutes;

[0030] (6) Add a foaming agent in an amount of 200-390 g / t to the ore pulp to which the collector has been added. After stirring for 1-3 min, turn on the aeration switch and then scrape the foam for 4-7 min. Filter the scraped foam and dry it at 105° C. to obtain No. 1 flake graphite concentrate, and the rest is tailings.

[0031] Preferably, the present invention provides a method for selectively flotating and purifying natural flake graphite by modified water glass, wherein the second scheme comprises the following steps:

[0032] (A) crushing a natural flake graphite ore having a fixed carbon content of 35% or more to 80% or more by a crusher to obtain a coarse crushed product, and then crushing it to 0.1 to 3 mm by a crushing and screening machine to obtain a fine crushed product, and grinding the fine crushed product by a sample preparation mill for 3 to 5 minutes, and the grinding particle size of -200 mesh accounts for more than 80%, thereby obtaining a flake graphite ore;

[0033] (B) transferring the flake graphite ore obtained in step (A) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 20 wt.%, and stirring for 1 to 3 minutes to obtain a pulp;

[0034] (C) adding a pH adjuster to the slurry obtained in step (B) to adjust the pH of the slurry to 9 to 11, and stirring for 2 to 5 minutes;

[0035] (D) After the salt and water glass are modified, 600-900 g / t of salt-modified water glass is added to the slurry after pH adjustment, and stirred for 2-5 minutes. The amount here is calculated based on the water glass before modification;

[0036] (E) adding a collector in an amount of 360 to 540 g / t to the slurry to which the salt-modified water glass is added, and stirring for 2 to 5 minutes;

[0037] (F) Adding a foaming agent in an amount of 220-450 g / t to the ore pulp to which the collector has been added, and after stirring for 1-3 minutes, turning on the aeration switch, and then scraping the foam for 5-8 minutes, filtering the scraped foam and drying it at 105° C. to obtain No. 2 flake graphite concentrate, and the rest is tailings.

[0038] In Option 1, the quartz content in the low-grade natural flake graphite ore with a fixed carbon content of less than or equal to 9% is greater than 20wt%.

[0039] In Option 2, the quartz content in the natural flake graphite ore having a fixed carbon content greater than or equal to 35% is less than or equal to 20wt%.

[0040] When used in industry, the crusher can be a jaw crusher, and the crushing and screening machine can be a roller crushing and screening machine.

[0041] The water used is preferably deionized water, and the flotation machine used can be an XFG5-35 hanging tank flotation machine. Of course, other bubbling flotation equipment can be used in the present invention.

[0042] The stirring process of Scheme 1 and Scheme 2 can be stirred by using a flotation machine impeller, with a rotation speed of 1200-1900 r / min, including 1200-1800 r / min and 1400-1900 r / min.

[0043] The pH adjusters used were HCl and NaOH.

[0044] In the present invention, in scheme 1, the acid used for acidifying and modifying the water glass is at least one of sulfuric acid and oxalic acid, wherein the mass ratio of the acid to the water glass is 1:1 to 1:3.

[0045] The preparation method of the acidified modified water glass is as follows: firstly, the ratio of water glass to acid is determined, then the water glass solution and the acid solution are diluted respectively and stirred evenly, and ultrasonic treatment is performed for 3 to 7 minutes under the ultrasonic condition of a frequency of 20 KHz and a power of 200 W during stirring, and then a water glass standard solution and an acid standard solution are prepared respectively, and then the water glass standard solution and the acid standard solution are mixed and stirred evenly according to the required ratio, and ultrasonic treatment is performed for 8 to 12 minutes under the ultrasonic condition of a frequency of 20 KHz and a power of 200 W during stirring, so as to finally obtain the acidified modified water glass solution.

[0046] In the present invention, in the second scheme, the salt used for the salt-modified water glass is Al 2 (SO 4 ) 3 、ZnSO 4 、AlCl 3 and FeCl 3 At least one of the following, wherein the mass ratio of salt to water glass is 1:1 to 1:4.

[0047] The preparation method of the salt-modified water glass is as follows: firstly, the ratio of water glass to salt is determined, then the water glass solution and the salt solution are diluted respectively and stirred evenly, and ultrasonic treatment is performed for 3 to 7 minutes under the ultrasonic condition of a frequency of 20 KHz and a power of 150 W during stirring, and then a water glass standard solution and a salt water standard solution are prepared respectively, and then the water glass standard solution and the salt water standard solution are mixed and stirred evenly according to the required ratio, and ultrasonic treatment is performed for 8 to 12 minutes under the ultrasonic condition of a frequency of 20 KHz and a power of 150 W during stirring, so as to finally obtain the salt-modified water glass solution.

[0048] The collector used is one of kerosene and diesel.

[0049] The foaming agent used is one of terpineol, methyl isobutyl carbinol and sec-octanol.

[0050] After turning on the air intake switch, the air intake volume is 30~80L / h, including 30~70L / h and 40~80L / h.

[0051] The obtained No. 1 flake graphite concentrate and No. 2 flake graphite concentrate are both graphite concentrates obtained by rough selection;

[0052] The fixed carbon content of the No. 1 graphite concentrate obtained by roughing is greater than or equal to 69%, and the fixed carbon content of the No. 1 graphite concentrate obtained after optimization is greater than or equal to 71%. The No. 1 graphite concentrate obtained by roughing is finely concentrated in 475g / t of acidified modified water glass, 145g / t of collector kerosene and 150g / t of foaming agent pine alcohol. After three times of fine concentration, the fixed carbon content in the graphite concentrate is increased to more than 93.5%.

[0053] The fixed carbon content of the No. 2 graphite concentrate obtained by roughing is greater than or equal to 83%. The fixed carbon content of the No. 2 graphite concentrate obtained after optimization is greater than or equal to 84%. The No. 2 graphite concentrate obtained by roughing is finely concentrated in 400g / t of salt-modified water glass, 190g / t of collector kerosene and 140g / t of foaming agent pine alcohol. After two times of fine concentration, the fixed carbon content in the graphite concentrate is increased to greater than or equal to 95%.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] The present invention adopts acid to carry out acidification modification treatment on water glass. After the acid is added into the water glass solution, the hydrolysis of sodium silicate therein is promoted to move in the direction of generating silicate colloid particles. The silicate colloid particles have strong activity and hydrophilicity and are more selective in the process of inhibiting minerals. In addition, the water glass is assisted with ultrasonic treatment in the modification process, so that the modified water glass molecules are finer and have better dispersibility. Moreover, the water glass has stronger selectivity for flake graphite ore and gangue minerals with high quartz content and low fixed carbon content, and can better inhibit the floating of gangue minerals, thereby greatly improving the fixed carbon content of flake graphite flotation concentrate and its recovery rate.

[0056] The present invention adopts salt to perform salt modification treatment on water glass, and the modification process is supplemented with ultrasonic treatment on the water glass, so that the modified water glass molecules are smaller and have better dispersibility, and the selectivity for flake graphite ore and gangue minerals with less quartz content and higher fixed carbon content is stronger, and the floating of gangue minerals can be better inhibited, and the fixed carbon content and recovery rate of flake graphite flotation concentrate are greatly improved.

[0057] The present invention adopts different modified water glasses for different graphite ores for the first time, and obtains products with high fixed carbon content and high recovery rate through the coordination of flotation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a flow chart of scheme 1 of the present invention.

[0059] Figure 2 This is a flow chart of scheme 2 of the present invention. DETAILED DESCRIPTION

[0060] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0061] The specific implementation modes of the present invention are further described below in conjunction with embodiments, but the present invention is not limited to the scope of the embodiments.

[0062] Example 1 of Scheme 1

[0063] The natural flake graphite ore produced in the Inner Mongolia mining area has impurities mainly composed of mica and quartz (quartz content is about 55.34wt%), and its composition is shown in Table 1.

[0064] Table 1 Composition of natural flake graphite in a mining area in Inner Mongolia

[0065]

[0066] The natural flake graphite ore is first crushed by an XPC-100X60 jaw crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by an XPS-Ф250×150 roller crusher and screener to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground by a sample preparation mill for 4 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0067] 1 ml of water glass and 1 ml of sulfuric acid (including H 2 SO 4 The mass fraction of the water glass is 95-98%), diluted with deionized water, and then stirred evenly, and ultrasonically treated for 5 minutes under the ultrasonic condition of a frequency of 20KHz and a power of 200W during stirring, and then prepared into a water glass standard solution and a sulfuric acid standard solution respectively in a 50ml volumetric flask, and then the water glass standard solution and the sulfuric acid standard solution are mixed and stirred in a mass ratio of sulfuric acid: water glass = 1:3, and ultrasonically treated for 10 minutes under the ultrasonic condition of a frequency of 20KHz and a power of 200W during stirring, to finally obtain an acidified modified water glass solution.

[0068] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 16 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6, and stirred for 3 minutes;

[0069] Acid modified water glass is added into the flotation tank at a dosage of 950 g / t of water glass before modification, and stirred for 3 minutes; then kerosene as a collector is added at a dosage of 290 g / t, and stirred for 3 minutes; then pine oil as a foaming agent is added at a dosage of 300 g / t, and after stirring for 2 minutes, the inflation switch is turned on, the air intake is set to 40 L / h, and then the foam is scraped for 6 minutes, the scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0070] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 74.38% and recovery rate of 85.17%. That is, the fixed carbon content of the graphite concentrate obtained by roughing was 74.38% and the graphite recovery rate was 85.17%.

[0071] The graphite concentrate obtained by rough selection was refined in 475g / t of acidified modified water glass, 145g / t of collector kerosene and 150g / t of foaming agent pinene alcohol. After three times of refinement, the fixed carbon content in the graphite concentrate increased to 94.81%.

[0072] Example 2 of Scheme 1

[0073] The natural flake graphite ore produced in a mining area in Henan Province has impurities mainly composed of mica, quartz, feldspar and pyrite (quartz content is about 43.02wt%), and its composition is shown in Table 2.

[0074] Table 2 Composition of natural flake graphite in a mining area in Henan

[0075]

[0076] The natural flake graphite ore is first crushed to 8-35 mm by an XPC-100X60 jaw crusher, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed to 0.1-3 mm by an XPS-Ф250×150 roller crusher and screener, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground for 3 minutes by a sample preparation mill, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0077] 1 ml of water glass and 1 ml of sulfuric acid were respectively diluted with deionized water, and then stirred evenly respectively. During stirring, ultrasonic treatment was performed for 5 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W. Then, a water glass standard solution and a sulfuric acid standard solution were respectively prepared in a 50 ml volumetric flask. Then, the water glass standard solution and the sulfuric acid standard solution were mixed and stirred evenly in a ratio of sulfuric acid: water glass = 1:2. During stirring, ultrasonic treatment was performed for 10 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W, and finally an acidified modified water glass solution was obtained.

[0078] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 20 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6.5, and stirred for 3 minutes;

[0079] Acidified modified water glass is added into the flotation tank at a dosage of 900 g / t of water glass before modification, and stirred for 3 minutes; then 320 g / t of collector diesel is added, and stirred for 3 minutes; then 330 g / t of foaming agent methyl isobutyl carbinol is added, and after stirring for 2 minutes, the inflation switch is turned on, the air intake is set to 50 L / h, and then scraping and foaming is performed for 7 minutes. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0080] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 71.91% and recovery rate of 86.32%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 71.91% and the graphite recovery rate was 86.32%.

[0081] The graphite concentrate obtained by rough selection is refined in 450g / t of acidified modified water glass, 160g / t of collector diesel and 165g / t of foaming agent methyl isobutyl carbinol. After three times of refinement, the fixed carbon content in the graphite concentrate is increased to 93.99%.

[0082] Embodiment 3 of Scheme 1

[0083] The natural flake graphite ore produced in a mining area in Henan Province has impurities mainly composed of mica, quartz and feldspar (quartz content is 56.57wt%), and its composition is shown in Table 3.

[0084] Table 3 Composition of natural flake graphite in a mining area in Henan

[0085]

[0086] The natural flake graphite ore is first crushed to 8-35 mm by an XPC-100X60 jaw crusher, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed to 0.1-3 mm by an XPS-Ф250×150 roller crusher and screener, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground for 3 minutes by a sample preparation mill, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0087] 1 ml of water glass and 1 ml of oxalic acid were respectively diluted with deionized water, and then stirred evenly respectively. During stirring, ultrasonic treatment was performed for 5 minutes under ultrasonic conditions of a frequency of 20 KHz and a power of 200 W. Then, a water glass standard solution and an oxalic acid standard solution were respectively prepared in a 50 ml volumetric flask. Then, the water glass standard solution and the oxalic acid standard solution were mixed and stirred evenly in a ratio of oxalic acid: water glass = 1:3. During stirring, ultrasonic treatment was performed for 10 minutes under ultrasonic conditions of a frequency of 20 KHz and a power of 200 W to finally obtain an acidified modified water glass solution.

[0088] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 22 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 7.5, and stirred for 3 minutes;

[0089] Acidified modified water glass is added into the flotation tank at a dosage of 1100 g / t of water glass before modification, and stirred for 3 minutes; then kerosene as a collector is added at a dosage of 270 g / t, and stirred for 3 minutes; then 240 g / t of octanol as a foaming agent is added, and after stirring for 2 minutes, the aeration switch is turned on, the air intake is set to 55 L / h, and then the foam is scraped for 5 minutes, the scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0090] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 69.27% ​​and recovery rate of 78.63%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 69.27% ​​and the graphite recovery rate was 78.63%.

[0091] The graphite concentrate obtained by rough selection was refined in 550g / t of acidified modified water glass, 135g / t of collector kerosene and 120g / t of foaming agent octanol. After four times of refinement, the fixed carbon content in the graphite concentrate increased to 95.21%.

[0092] Comparative Example 1 of Scheme 1

[0093] The other conditions are the same as those in the roughing process of Example 1, except that the water glass is not subjected to acidification modification treatment:

[0094] The natural flake graphite ore is first crushed by an XPC-100X60 jaw crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by an XPS-Ф250×150 roller crusher and screener to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground by a sample preparation mill for 4 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0095] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 16 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6, and stirred for 3 minutes;

[0096] Add 950g / t of water glass into the flotation tank and stir for 3min; then add 290g / t of kerosene as a collector and stir for 3min; then add 300g / t of pine oil as a foaming agent. After stirring for 2min, turn on the aeration switch, set the air intake to 40L / h, and then scrape and foam for 6min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0097] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 49.43% and recovery rate of 51.09%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 49.43% and the graphite recovery rate was 51.09%.

[0098] Comparative Example 2 of Scheme 1

[0099] The other conditions are the same as those in Example 1, except that the ratio of acid to water glass in the modified water glass ratio is not within the protection range of 1:1 to 1:3 of the present invention, namely:

[0100] The natural flake graphite ore is first crushed by an XPC-100X60 jaw crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by an XPS-Ф250×150 roller crusher and screener to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground by a sample preparation mill for 4 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0101] 1 ml of water glass and 1 ml of sulfuric acid were respectively diluted with deionized water, and then stirred evenly respectively. During stirring, ultrasonic treatment was performed for 5 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W. Then, a water glass standard solution and a sulfuric acid standard solution were respectively prepared in a 50 ml volumetric flask. Then, the water glass standard solution and the sulfuric acid standard solution were mixed and stirred evenly in a ratio of sulfuric acid: water glass = 2:1. During stirring, ultrasonic treatment was performed for 10 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W, and finally an acidified modified water glass solution was obtained.

[0102] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 16 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6, and stirred for 3 minutes;

[0103] Acid modified water glass is added into the flotation tank at a dosage of 950 g / t of water glass before modification, and stirred for 3 minutes; then kerosene as a collector is added at a dosage of 290 g / t, and stirred for 3 minutes; then pine oil as a foaming agent is added at a dosage of 300 g / t, and after stirring for 2 minutes, the inflation switch is turned on, the air intake is set to 40 L / h, and then the foam is scraped for 6 minutes, the scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0104] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 47.35%, recovery rate of 32.81%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 47.35%, and the graphite recovery rate was 32.81%.

[0105] Comparative Example 3 of Scheme 1

[0106] The other conditions are the same as those in Example 1, except that the amount of modified water glass is not within the protection range of the present invention of 700 to 1100 g / t, that is:

[0107] The natural flake graphite ore is first crushed by an XPC-100X60 jaw crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by an XPS-Ф250×150 roller crusher and screener to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the obtained finely crushed product is ground by a sample preparation mill for 4 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore;

[0108] 1 ml of water glass and 1 ml of sulfuric acid were respectively diluted with deionized water, and then stirred evenly respectively. During stirring, ultrasonic treatment was performed for 5 minutes under ultrasonic conditions of a frequency of 20 KHz and a power of 200 W. Then, a water glass standard solution and a sulfuric acid standard solution were respectively prepared in a 50 ml volumetric flask. Then, the water glass standard solution and the sulfuric acid standard solution were mixed and stirred evenly according to a ratio of sulfuric acid: water glass = 1:3. During stirring, ultrasonic treatment was performed for 10 minutes under ultrasonic conditions of a frequency of 20 KHz and a power of 200 W, and finally an acidified modified water glass solution was obtained.

[0109] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 16 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6, and stirred for 3 minutes;

[0110] Acid modified water glass is added into the flotation tank at a dosage of 1300 g / t of water glass before modification, and stirred for 3 min; then kerosene as a collector is added at a dosage of 290 g / t, and stirred for 3 min; then pine oil as a foaming agent is added at a dosage of 300 g / t, and after stirring for 2 min, the aeration switch is turned on, the air intake is set to 40 L / h, and then the foam is scraped for 6 min, the scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0111] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 61.75%, recovery rate of 56.31%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 61.75%, and the graphite recovery rate was 56.31%.

[0112] Comparative Example 4

[0113] Other conditions are the same as those in Example 1, except that:

[0114] 1 ml of water glass and 1 g of Al 2 (SO 4 ) 3 The mixture was diluted with deionized water, and then stirred evenly, and ultrasonically treated for 5 minutes under an ultrasonic condition of 20 KHz and 150 W during stirring, and then prepared into a water glass standard solution and an aluminum sulfate standard solution respectively in a 50 ml volumetric flask, and then the water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to a ratio of aluminum sulfate: water glass = 1:2, and ultrasonically treated for 10 minutes under an ultrasonic condition of 20 KHz and 150 W during stirring, and finally a salinized modified water glass solution was obtained;

[0115] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 16 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 6, and stirred for 3 minutes;

[0116] Add 950g / t of salt-modified water glass to the flotation tank and stir for 3 minutes; then add 290g / t of collector kerosene and stir for 3 minutes; then add 300g / t of foaming agent pine oil. After stirring for 2 minutes, turn on the inflation switch, set the air intake to 40L / h, and then scrape for 7 minutes. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0117] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 58.20% and recovery rate of 59.77%.

[0118] Solution 2 - Example 4

[0119] The natural flake graphite ore produced in the Hunan mining area has impurities mainly consisting of mica and albite (quartz content is 8.16wt%), and the fixed carbon content of the original ore is 44.62%.

[0120] The natural flake graphite ore in the Hunan mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0121] 1 ml of water glass and 1 g of Al 2 (SO 4 ) 3 The mixture was diluted with deionized water, and then stirred evenly. During stirring, the mixture was ultrasonically treated for 5 minutes under the ultrasonic conditions of 20 KHz and 150 W. Then, a water glass standard solution and an aluminum sulfate standard solution were prepared in a 50 ml volumetric flask. The water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to the ratio of aluminum sulfate: water glass = 1:2. During stirring, the mixture was ultrasonically treated for 10 minutes under the ultrasonic conditions of 20 KHz and 150 W. Finally, a salt-modified water glass solution was obtained.

[0122] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 15 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0123] Add 800g / t of salt-modified water glass to the flotation tank and stir for 3min; then add 380g / t of collector kerosene and stir for 3min; then add 280g / t of foaming agent pine oil. After stirring for 2min, turn on the inflation switch, set the air intake to 50L / h, and then scrape for 7min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0124] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 85.91% and recovery rate of 83.34%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 85.91% and the graphite recovery rate was 83.34%.

[0125] The graphite concentrate obtained by rough selection is refined in 400g / t of salt-modified water glass, 190g / t of collector kerosene and 140g / t of foaming agent pinene alcohol. After two rounds of refinement, the fixed carbon content in the graphite concentrate is increased to 95.17%.

[0126] Solution 2 - Example 5

[0127] The natural flake graphite ore produced in the Inner Mongolia mining area has impurities mainly composed of mica, albite and pyrite (quartz content is 12.31wt%), and the fixed carbon content of the original ore is 38.71%.

[0128] The natural flake graphite ore in the Inner Mongolia mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0129] 1 ml of water glass and 1 g of AlCl 3 The mixture was diluted with deionized water, and then stirred evenly. During stirring, the mixture was ultrasonically treated for 5 minutes under the ultrasonic conditions of 20 KHz and 150 W. Then, a water glass standard solution and an aluminum sulfate standard solution were prepared in a 50 ml volumetric flask. The water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to the ratio of aluminum chloride: water glass = 2:3. During stirring, the mixture was ultrasonically treated for 10 minutes under the ultrasonic conditions of 20 KHz and 150 W. Finally, a salt-modified water glass solution was obtained.

[0130] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 20 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0131] Add 900g / t of salted modified water glass to the flotation tank and stir for 3min; then add 360g / t of collector diesel and stir for 3min; then add 270g / t of foaming agent pine oil. After stirring for 2min, turn on the inflation switch, set the air intake to 60L / h, and then scrape for 7min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0132] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 84.11% and recovery rate of 82.09%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 84.11% and the graphite recovery rate was 82.09%.

[0133] The graphite concentrate obtained by rough selection is refined in 450g / t of salt-modified water glass, 180g / t of collector kerosene and 135g / t of foaming agent pinene alcohol. After three times of refinement, the fixed carbon content in the graphite concentrate is increased to 95.60%.

[0134] Solution 2 - Example 6

[0135] The natural flake graphite ore produced in the Henan mining area has impurities mainly composed of mica, potassium feldspar and pyrite (quartz content is 6.97wt%), and the fixed carbon content of the original ore is 49.03%.

[0136] The natural flake graphite ore in the Henan mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0137] 1 ml of water glass and 1 g of ZnSO 4 The mixture was diluted with deionized water, and then stirred evenly. During stirring, the mixture was ultrasonically treated for 5 minutes under the ultrasonic conditions of 20 KHz and 150 W. Then, a water glass standard solution and an aluminum sulfate standard solution were prepared in a 50 ml volumetric flask. The water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to the ratio of zinc sulfate: water glass = 1:3. During stirring, the mixture was ultrasonically treated for 10 minutes under the ultrasonic conditions of 20 KHz and 150 W. Finally, a salt-modified water glass solution was obtained.

[0138] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 18 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 9, and stirred for 3 minutes;

[0139] Add 820g / t of salted modified water glass to the flotation tank and stir for 3min; then add 340g / t of collector kerosene and stir for 3min; then add 260g / t of foaming agent octanol, after stirring for 2min, turn on the aeration switch, set the air intake to 60L / h, and then scrape for 8min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0140] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 86.23% and recovery rate of 83.07%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 86.23% and the graphite recovery rate was 83.07%.

[0141] The graphite concentrate obtained by rough selection is refined in 410g / t of salt-modified water glass, 170g / t of collector kerosene and 130g / t of foaming agent pinene alcohol. After two rounds of refinement, the fixed carbon content in the graphite concentrate is increased to 96.12%.

[0142] Scheme 2-Comparative Example 5

[0143] The other conditions are the same as those in Example 4, except that the water glass is not subjected to salt modification treatment:

[0144] The natural flake graphite ore in the Hunan mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0145] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 15 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0146] Add 800g / t of water glass before modification into the flotation tank and stir for 3min; then add 380g / t of collector kerosene and stir for 3min; then add 280g / t of foaming agent pine oil. After stirring for 2min, turn on the inflation switch, set the air intake to 50L / h, and then scrape for 7min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0147] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 59.82% and recovery rate of 52.10%, that is, the fixed carbon content of the graphite concentrate obtained by roughing was 59.82% and the graphite recovery rate was 52.10%.

[0148] Scheme 2-Comparative Example 6

[0149] The other conditions are the same as those in Example 4, except that the ratio of salt to water glass in the modified water glass ratio is not within the protection range of the present invention of 1:1 to 1:4, that is:

[0150] The natural flake graphite ore in the Hunan mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0151] 1 ml of water glass and 1 g of Al 2 (SO 4 ) 3 The mixture was diluted with deionized water, and then stirred evenly. During stirring, the mixture was ultrasonically treated for 5 minutes under the ultrasonic conditions of 20 KHz and 150 W. Then, a water glass standard solution and an aluminum sulfate standard solution were prepared in a 50 ml volumetric flask. The water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to the ratio of aluminum sulfate: water glass = 3:1. During stirring, the mixture was ultrasonically treated for 10 minutes under the ultrasonic conditions of 20 KHz and 150 W. Finally, a salt-modified water glass solution was obtained.

[0152] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 15 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0153] Add 800g / t of salt-modified water glass to the flotation tank and stir for 3min; then add 380g / t of collector kerosene and stir for 3min; then add 280g / t of foaming agent pine oil. After stirring for 2min, turn on the inflation switch, set the air intake to 50L / h, and then scrape for 7min. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0154] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 57.34% and recovery rate of 54.62%.

[0155] Scheme 2-Comparative Example 7

[0156] The other conditions are the same as those in Example 4, except that the amount of modified water glass is not within the protection range of the present invention of 600 to 900 g / t, namely:

[0157] The natural flake graphite ore in the Hunan mining area is coarsely crushed by a crusher to 8-35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1-3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 minutes, and the grinding particle size is -200 mesh, accounting for more than 80%, to obtain flake graphite ore;

[0158] 1 ml of water glass and 1 g of Al 2 (SO 4 ) 3 The mixture was diluted with deionized water, and then stirred evenly. During stirring, the mixture was ultrasonically treated for 5 minutes under the ultrasonic conditions of 20 KHz and 150 W. Then, a water glass standard solution and an aluminum sulfate standard solution were prepared in a 50 ml volumetric flask. The water glass standard solution and the aluminum sulfate standard solution were mixed and stirred evenly according to the ratio of aluminum sulfate: water glass = 1:2. During stirring, the mixture was ultrasonically treated for 10 minutes under the ultrasonic conditions of 20 KHz and 150 W. Finally, a salt-modified water glass solution was obtained.

[0159] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 15 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0160] Add 500g / t of salt-modified water glass to the flotation tank and stir for 3 minutes; then add 380g / t of collector kerosene and stir for 3 minutes; then add 280g / t of foaming agent pine oil. After stirring for 2 minutes, turn on the inflation switch, set the air intake to 50L / h, and then scrape for 7 minutes. The scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0161] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 56.83% and recovery rate of 72.91%.

[0162] Comparative Example 8

[0163] The raw materials and other conditions are the same as those in Example 4, except that:

[0164] 1 ml of water glass and 1 ml of sulfuric acid were respectively diluted with deionized water, and then stirred evenly respectively. During stirring, ultrasonic treatment was performed for 5 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W. Then, a water glass standard solution and a sulfuric acid standard solution were respectively prepared in a 50 ml volumetric flask. Then, the water glass standard solution and the sulfuric acid standard solution were mixed and stirred evenly in a ratio of sulfuric acid: water glass = 2:1. During stirring, ultrasonic treatment was performed for 10 minutes under ultrasonic conditions with a frequency of 20 KHz and a power of 200 W, and finally an acidified modified water glass solution was obtained.

[0165] The flake graphite ore obtained by grinding is transferred to a flotation tank and mixed with water at a pulp concentration of 15 wt.%, and stirred for 3 minutes to obtain a pulp, a pH adjuster is added to the obtained pulp, the pH of the pulp is adjusted to 10, and the pulp is stirred for 3 minutes;

[0166] The acidified modified water glass solution is added into the flotation tank at a dosage of 800 g / t of the water glass before modification, and stirred for 3 minutes; then the collector kerosene is added at a dosage of 380 g / t, and stirred for 3 minutes; then the foaming agent pine oil is added at a dosage of 280 g / t, and after stirring for 2 minutes, the inflation switch is turned on, the air intake is set to 50 L / h, and then the foam is scraped for 7 minutes, the scraped foam is filtered and dried at 105°C to obtain flake graphite concentrate, and the rest is tailings.

[0167] During the flotation process, natural flake graphite ore was flotated at room temperature. The indicators of the flotation products obtained through continuous expansion tests were: fixed carbon content of 78.63% and recovery rate of 81.26%.

Claims

1. A method for purifying natural flake graphite by selective flotation of modified water glass, comprising the following schemes; Solution 1 (1) crushing and grinding a low-grade natural flake graphite ore having a fixed carbon content of 9% or less until the grinding particle size of -200 mesh accounts for more than 90% to obtain flake graphite ore powder; (2) transferring the flake graphite ore powder obtained in step (1) to a flotation tank and mixing it with water at a slurry concentration of 10 wt.% to 22 wt.%, stirring to obtain a slurry; (3) adding a pH adjuster to the slurry obtained in step (2) to adjust the pH of the slurry to 5 to 8, and stirring to obtain a slurry with adjusted pH; (4) Adding acidified modified water glass in an amount of 700-1100 g / t to the slurry after pH adjustment and stirring. The amount here is calculated based on the water glass before modification; (5) adding a collector in an amount of 270 to 420 g / t to the slurry containing acidified modified water glass obtained in step (4), and stirring; (6) adding a frother in an amount of 200 to 390 g / t to the slurry to which the collector is added obtained in step (5), stirring, turning on the aeration switch, and then performing flotation by scraping, filtering and drying the scraped foam to obtain No. 1 flake graphite concentrate; Solution 2 (A) crushing and grinding natural flake graphite ore having a fixed carbon content of 35% or more until the grinding particle size of -200 mesh accounts for more than 80% to obtain flake graphite ore powder; (B) transferring the raw graphite flake powder obtained in step (A) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 20 wt.%, stirring to obtain a pulp; (C) adding a pH adjuster to the slurry obtained in step (B) to adjust the pH of the slurry to 9 to 11, and stirring; (D) adding 600-900 g / t of salt-modified water glass to the pH-adjusted slurry obtained in step (C), and stirring, wherein the amount is calculated based on the water glass before modification; (E) adding a collector in an amount of 360 to 540 g / t to the slurry containing salt-modified water glass obtained in step (D), and stirring; (F) adding a frother in an amount of 220-450 g / t to the ore pulp to which the collector is added obtained in step (E), stirring, turning on the aeration switch, and then performing flotation by scraping, filtering and drying the scraped foam to obtain No. 2 flake graphite concentrate.

2. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: Solution 1 includes the following steps: (1) A low-grade natural flake graphite ore having a fixed carbon content of 9% or less is coarsely crushed by a crusher to 8 to 35 mm, accounting for more than 80%, to obtain a coarse crushed product, and then finely crushed by a crushing and screening machine to 0.1 to 3 mm, accounting for more than 80%, to obtain a finely crushed product, and the finely crushed product is ground by a sample preparation mill for 3 to 5 minutes, and the grinding particle size is -200 mesh, accounting for more than 90%, to obtain flake graphite ore; (2) transferring the flake graphite ore obtained in step (1) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 22 wt.%, and stirring for 1 to 3 minutes to obtain a pulp; (3) adding a pH adjuster to the slurry obtained in step (2) to adjust the pH of the slurry to 5 to 8, and stirring for 2 to 5 minutes; (4) After the acid and water glass are modified, 700-1100 g / t of acidified modified water glass is added to the pH-adjusted slurry and stirred for 2-5 min. The amount here is calculated based on the water glass before modification. (5) adding a collector in an amount of 270 to 420 g / t to the slurry to which the acidified modified water glass is added, and stirring for 2 to 5 minutes; (6) Add a foaming agent in an amount of 200-390 g / t to the ore pulp to which the collector has been added. After stirring for 1-3 min, turn on the aeration switch and then scrape the foam for 4-7 min. Filter the scraped foam and dry it at 105° C. to obtain No. 1 flake graphite concentrate, and the rest is tailings.

3. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: Solution 2 includes the following steps: (A) crushing a natural flake graphite ore having a fixed carbon content of 35% or more to 80% or more by a crusher to obtain a coarse crushed product, and then crushing it to 0.1 to 3 mm by a crushing and screening machine to obtain a fine crushed product, and grinding the fine crushed product by a sample preparation mill for 3 to 5 minutes, and the grinding particle size of -200 mesh accounts for more than 80%, thereby obtaining a flake graphite ore; (B) transferring the flake graphite ore obtained in step (A) to a flotation tank and mixing it with water at a pulp concentration of 10 wt.% to 20 wt.%, and stirring for 1 to 3 minutes to obtain a pulp; (C) adding a pH adjuster to the slurry obtained in step (B) to adjust the pH of the slurry to 9 to 11, and stirring for 2 to 5 minutes; (D) After the salt and water glass are modified, 600-900 g / t of salt-modified water glass is added to the slurry after pH adjustment, and stirred for 2-5 minutes. The amount here is calculated based on the water glass before modification; (E) adding a collector in an amount of 360 to 540 g / t to the slurry to which the salt-modified water glass is added, and stirring for 2 to 5 minutes; (F) Adding a foaming agent in an amount of 220-450 g / t to the ore pulp to which the collector has been added, and after stirring for 1-3 minutes, turning on the aeration switch, and then scraping the foam for 5-8 minutes, filtering the scraped foam and drying it at 105° C. to obtain No. 2 flake graphite concentrate, and the rest is tailings.

4. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: In scheme 1, the quartz content in the low-grade natural flake graphite ore with a fixed carbon content of 9% or less is greater than 20wt%; In Option 2, the quartz content in the natural flake graphite ore having a fixed carbon content greater than or equal to 35% is less than or equal to 20wt%.

5. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: The mixing process of Scheme 1 and Scheme 2 can be stirred by the impeller of the flotation machine with a speed of 1200-1900r / min; The pH adjusters used were HCl and NaOH.

6. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: In the first scheme, the acid used for acidifying and modifying the water glass is at least one of sulfuric acid and oxalic acid, wherein the mass ratio of the acid to the water glass is 1:1 to 1:

3.

7. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: In the second scheme, the salt used for the salt-modified water glass is at least one of Al2(SO4)3, ZnSO4, AlCl3 and FeCl3, wherein the mass ratio of the salt to the water glass is 1:1 to 1:

4.

8. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: The collector used is one of kerosene and diesel; The foaming agent used is one of terpineol, methyl isobutyl carbinol and sec-octanol; After turning on the air intake switch, the air intake volume is 30~80L / h.

9. The method for purifying natural flake graphite by selective flotation of modified water glass according to claim 1, characterized in that: The obtained No. 1 flake graphite concentrate and No. 2 flake graphite concentrate are both graphite concentrates obtained by rough selection; The fixed carbon content of the No. 1 graphite concentrate obtained by roughing is greater than or equal to 69%, and the fixed carbon content of the No. 1 graphite concentrate obtained after optimization is greater than or equal to 71%. The No. 1 graphite concentrate obtained by roughing is finely concentrated in 475g / t of acidified modified water glass, 145g / t of collector kerosene and 150g / t of foaming agent pine alcohol. After three times of fine concentration, the fixed carbon content in the graphite concentrate is increased to more than 93.5%; The fixed carbon content of the No. 2 graphite concentrate obtained by roughing is greater than or equal to 83%. The fixed carbon content of the No. 2 graphite concentrate obtained after optimization is greater than or equal to 84%. The No. 2 graphite concentrate obtained by roughing is finely concentrated in 400g / t of salt-modified water glass, 190g / t of collector kerosene and 140g / t of foaming agent pine alcohol. After two times of fine concentration, the fixed carbon content in the graphite concentrate is increased to greater than or equal to 95%.

Citation Information

Patent Citations

  • Low-grade aphanitic graphite dressing and purifying method

    CN103072975A

  • Flotation column flotation method of flake graphite

    CN105583086A

  • Beneficiation method of protection scale for fine grained graphite ore

    CN109909062A

  • AU2020104144A4